Color calibration of digital images for improvement of movement analysis - Rozinek, Ondřej; Szabó, Zoltán (Lékař a technika, 2008)
Two video sequences of hand motion are analyzed using passive markers for medical diagnostic purposes. Th e correct detection of the marker's position is essential for the next motion evaluation step. GretagMacbeth ColorChecker chart is used for color correction of the video sequences, compensation of diff erent contrast, and brightness conditions during the motion recording. Diff erent color calibration methods were compared based on linear, and cubic Hermite functions, and the multiple linear regression model. Th eir effi ciencies were evaluated from the movement analysis point of view. Th e best results were achieved with multiple linear regression model.
Keywords: Diagnostic Techniques and Procedures; Diagnostic Imaging; Color; Video Recording; Hand; regresní analýza; diagnostické techniky a postupy; pohyb; teoretické modely; ruka; Image Processing, Computer-Assisted; lineární modely; audiovizuální záznam; Models, Theoretical; počítačové zpracování obrazu; lidé; Humans; Movement; barva; Linear Models; Financing, Organized; Regression Analysis; financování organizované; diagnostické zobrazování